Figurações do gaúcho na ficção rio-grandense do século XIX - Steindorff, Jordana Cassel (2017)
Much has already been said and much remains to say about the inhabitants of Rio Grande do Sul. Regionalism, as an artistic current inspired by regional links, has always advocated for the preservation of the cultural and artistic heritage of the remote regions of Brazilian immensity. In the extreme south, it pointed in the letters, riding a representative type in affirmation, to perpetuate a retempered history by an ethnic horizon perfectly identified with geography. From the mix of different peoples, of those who arrived in the Província de São Pedro with those who were native here, sprouted, adorned by the pampas exuberance, the gaucho’s figure. This type wandered from a pejorative connotation, from clandestinity and poverty, to the rank of trooper, warrior and even hero. Our objecctive, in this research, is to develop an analysis from two literary pieces, in order to reflect and demonstrate the interventions that these productions have exerted to the gaucho's figuration. We believe in the authenticity of this work precisely for investing in a period which gaucho’s myth was being formed. We define as the corpus this work A divina pastora (1992), by José Antônio do Vale Caldre e Fião, and O vaqueano (1973), by Apolinário José Gomes Porto Alegre, since both authors significantly worked to the elaboration and development of a literary system in Rio Grande do Sul. Our research question consists in problematizing how nineteenth-century writers, especially the members of the Partenon Literário society, undertook the emancipation movement of regional literature, constructing the gaucho figuration in Rio Grande do Sul’s fiction. This temporal cut is justified by the political transformation existing in Brazil and, consequently, in Rio Grande do Sul in this period. Therefore, we suppose that fabric in this process, the gaucho’s social type is taken by literature as a hero, which includes values such as honesty, loyalty and bravery. Consequently, the analysis of the reality’s fictional transpositions makes possible the recomposition of the collective imaginary’s particularities from a time in the past, characteristics that take for granted an altered identity, that began to compose a symbolic world.